Strategic business models : idealism and realism in strategy - Betz, Frederick, 1937- (Emerald Publishing Limited, 2018)
Strategy needs to be partly idealistic and partly realistic. On the one hand, it exists to help managers and executives envision the most beneficial future possibleone that is optimally competitive and profitable. But such visualizing needs to go hand-in-hand with concrete planning. In order to formulate a strategy that will really work, organizations need to master the technique of modelling in order to plan what can properly be called strategic business model, a model that both depicts the operations of a business and that provides the analytical basis for examining and formulating the plan for the future operations of a firm. Here leading expert Frederick Betz reviews the strategic modelling technique and applies it to diverse kinds of businesses, both productive and financial, and including banks and hedge funds. He illustrates the possibilities of this techniqueand the pitfalls of using it incorrectlyby applying it to real business cases, some successful and some problematic. As strategic business models are important to understand the transformative operations of an enterprise system for present and future competitiveness, Betz's exploration into both manufacturing and financial firms, along with retailing firms and conglomerates, broadens the business literature. Strategic Business Models: Idealism and Realism in Strategy is essential reading for managers and strategists wishing to optimize the effectiveness of their strategic planning.- Resumé vydavatel